Single‐sweep pulmonary vein isolation using the new third‐generation laser balloon—Evolution in ablation style using endoscopic ablation system. (23rd September 2021) - Tohoku, Shota; Bordignon, Stefano; Chen, Shaojie; Zanchi, Simone; Bianchini, Lorenzo; Trolese, Luca; Operhalski, Felix; Urbanek, Lukas; Chun, K. R. Julian; Schmidt, Boris
Abstract: Background: The endoscopic ablation system (EAS) is an established ablation device for pulmonary vein isolation (PVI) in patients with atrial fibrillation (AF). The novel X3 EAS is now equipped with a contiguous circumferential ablation mode (RAPID mode). Aim: To determine the feasibility of single‐shot fashioned ablation using X3. Methods: Consecutive patients who underwent AF ablation using X3 were enrolled. We assessed the acute procedural data focusing on "Single‐sweep PVI" defined as successful PVI with a single RAPID mode energy application, and on "first‐pass isolation" defined as successful PVI after initial circular lesion set. Results: One hundred AF patients (56% male, age: 68 ± 10 years, 66% paroxysmal AF) were analyzed. A total of 379 of 383 PVs (99%) were isolated with X3. Single‐sweep PVI and first‐pass‐isolation were achieved in 214 PVs (56%) and in 362 PVs (95%), respectively. Single‐sweep PVI rates varied across PVs with higher rates at the superior PVs (61.2% vs. inferior PVs: 49.5%, p  = .0239) and at PVs with maximal ostial diameter <24 mm (57.6% vs. >24 mm: 36.8%, p  = .0151). The mean total procedure and fluoroscopy times were 43.0 ± 10 and 4.0 ± 2 min, respectively. In none of the patients an acute thromboembolic event (stroke or transient ischemic attack) or a pericardial effusion/tamponade occurred. A single transient phrenic nerve palsy was observed. Conclusion: The new X3 EAS allows for single‐shot fashioned ablation in terms of single‐sweep PVI in half or more of PVs. The new RAPID ablation mode leads to an improved rate of first‐pass isolation associated with very short procedure times without compromising safety.